Anterior pushing technique for a broken scalpel blade in lumbar discectomy: a case report - Čeleš, Dejan; Gasparini, Mladen; Mohar, Janez (Frontiers in Surgery, 2023)
The presence of broken surgical blades or other surgically uncontrolled sharp and pointed objects in the disc space is a rare but potentially severe complication of posterior lumbar spine procedures. Herein, we report the case of a 59-year-old female patient with a history of lumbar decompression and interspinous process device implantation who underwent an instrumented revision of the lumbosacral junction. During L5-S1 discectomy, the scalpel blade split, and the broken portion could not be reached from the posterior approach. Regarding the vascular anatomy, we partially pushed the fragment through the anterior annulus into the retroperitoneal space and locked pedicle screws, making the construct stable. The fractured blade segment was eventually removed by laparoscopy 1 week after the initial procedure. This experience suggests that the anterior pushing technique with fluoroscopy is an option in the rare event of a posteriorly unreachable broken scalpel blade. In such cases, computed tomography angiography is recommended.